EVALUASI PENERAPAN SISTEM INFORMASI AKUNTANSI PERSEDIAAN BAHAN BAKU PADA PT. CIOMAS ADISATWA MEDAN - Melky Alessandro Purba; Dimita H. P. Purba; Jamaluddin Jamaluddin; Mulatua P. Silalahi (Universitas Methodist Indonesia, 2021)
This study aims to determine the application of accounting information system for raw material inventories at PT. Ciomas Adisatwa Medan. To find out the application of the accounting system for raw material inventory at PT. Ciomas Adisatwa Medan, data collection techniques were used, namely literature study and field research techniques. While the analysis technique used is a descriptive method. From the results of the study, it can be concluded that application of the accounting information system for raw material inventory at PT. Ciomas Adisatwa Medan has been implemented not good, because there is still inaccurate information that is the demand for raw materials is not in accordance with what is received by the production. Weaknesses Oversight of raw material inventory in warehouses is piling up and is not suitable for processing. The delay in the schedule of order for supporting raw materials to be processed, so the production process does not run properly. The procedures used in the accounting information system for raw material inventory at PT. Ciomas Adisatwa Medan, among others, procedures for requesting raw materials, procedures for receiving raw materials and procedures for issuing raw materials.